THE INSTABILITY OF JOHN RAWLS'S "STABILITY FOR THE RIGHT REASONS". (22nd May 2017) - Chung, Hun
ABSTRACT: John Rawls's most mature notion of political order is "stability for the right reasons." Stability for the right reasons is the kind of political order that Rawls hoped a well-ordered society could ideally achieve. In this paper, I demonstrate through the tools of modern game theory, the instability of "stability for the right reasons." Specifically, I will show that a well-ordered society can completely destabilize by the introduction of an arbitrarily small number of non-compliers whenever individuals fail to achieve full common knowledge ever so slightly.